The Effect of Differences Color of Artificial Bait on Sepioteuthis lessosiana catches using Hand Line - Farhan Ramdhani; Lauura Hermala Yunita; Rizky Janatul Magwa; Ester Restiana Endang Gelis; Yoppie Wulanda (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Hand Line is a traditional fishing gear that commonly used by a fisherman in the Panggang Island, Kepulauan Seribu to catch bigfin reef squid (Sepioteuthis lessosiana). The purpose of this research is to analize the effect of color differences on artificial bait to catchment product of squid and to determine the bait’s colors that produce the most catches of squid. This research was conducted through an experimental method using a randomized block design (RAK) for 14 repetitions. Total of catches that earned amounted to 268 individuals (32,1 kg) consisted of 79 individuals (9,1 kg) caught with artificial baits orange color combination of white, 57 (7,7 kg) caught with artificial baits green color combination of white and 132 individuals (15,3 kg) caught with artificial bait color combination of red and white